Pengaruh Kualitas Produk dan Harga terhadap Loyalitas melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Produk Glad2Glow - Dena Salsabila; Emil Salim; Yosi Puspita sari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study investigates the influence of product quality and pricing on customer loyalty, with customer satisfaction acting as a mediating variable in the context of Glad2Glow skincare products. A quantitative approach employing a causal–associative research design was adopted. Data were obtained through structured questionnaires administered to 100 consumers of Glad2Glow products. The data were analyzed using Partial Least Squares–based Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.0. The findings indicate that both product quality and price exert a positive and significant effect on customer satisfaction. However, neither product quality nor price demonstrates a significant direct impact on customer loyalty. In contrast, customer satisfaction has a positive and significant effect on customer loyalty and serves as a mediating variable in the relationship between product quality, price, and customer loyalty.